Does the car make elderly people happy and mobile? Settlement structures, car availability and leisure mobility of the elderly - Scheiner, Joachim (European Journal of Transport and Infrastructure Research, 2006)
According to gerontological mobility research, appropriate settlement structures at the neighbourhood level and car availability are both playing a prominent role in the maintenance of mobility of elderly people. However, car availability is strongly connected to other individual attributes like age, health and gender. The paper presents empirical results from Germany, which support the thesis that car availability is not a cause for mobility, but rather a result of a specific life situation and way of life of elderly people, which is associated with a specific type of mobility. What is more, there is no evidence for a significant influence of settlement structures on mobility. The contribution is based on multiple regression analyses of leisure mobility of elderly people living in three different spatial contexts.